2012
DOI: 10.1001/archneurol.2011.1175
|View full text |Cite
|
Sign up to set email alerts
|

Brain Excitability in Stroke

Abstract: here is no current medical therapy for stroke recovery. Principles of physiological plasticity have been identified during recovery in both animal models and human stroke. Stroke produces a loss of physiological brain maps in adjacent peri-infarct cortex and then a remapping of motor and sensory functions in this region. This remapping of function in peri-infarct cortex correlates closely with recovery. Recent studies have shown that the stroke produces abnormal conditions of excitability in neuronal circuits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(105 citation statements)
references
References 36 publications
2
98
1
Order By: Relevance
“…This inter-hemispheric shift towards the unaffected hemisphere has been thought to be the sign of distress (Cramer et al, 2011). During stroke recovery (often occurring in the post-early stage of subacute phase and the chronic phase), however, the somatosensory motor activities responding to the affected limbs are transferred and reorganized in the ipsilesional cortex near the infarct area (Brown et al, 2009; Carmichael, 2012; Dijkhuizen et al, 2001; Sharma and Cohen, 2012; Tombari et al, 2004; Wang et al, 2010a). Many clinical studies have demonstrated that good motor functional recovery is associated with the increased functional activities in the ipsilesional motor cortex, whereas the patients with poor recovery show the involvement of the contralesional motor cortex during movement of the affected hand (Fridman et al, 2004; Sharma and Cohen, 2012; Werhahn et al, 2003).…”
Section: The Intrinsic Capability Of Brain Self-repair In Stroke Recomentioning
confidence: 99%
“…This inter-hemispheric shift towards the unaffected hemisphere has been thought to be the sign of distress (Cramer et al, 2011). During stroke recovery (often occurring in the post-early stage of subacute phase and the chronic phase), however, the somatosensory motor activities responding to the affected limbs are transferred and reorganized in the ipsilesional cortex near the infarct area (Brown et al, 2009; Carmichael, 2012; Dijkhuizen et al, 2001; Sharma and Cohen, 2012; Tombari et al, 2004; Wang et al, 2010a). Many clinical studies have demonstrated that good motor functional recovery is associated with the increased functional activities in the ipsilesional motor cortex, whereas the patients with poor recovery show the involvement of the contralesional motor cortex during movement of the affected hand (Fridman et al, 2004; Sharma and Cohen, 2012; Werhahn et al, 2003).…”
Section: The Intrinsic Capability Of Brain Self-repair In Stroke Recomentioning
confidence: 99%
“…Post-stroke investigations measuring currents, neurotransmitter receptor expression, MEG recordings, and fMRI signals have demonstrated either an increase in excitation [66-68] or a decrease of inhibition [67,69,70] (especially synaptic/phasic inhibition) [13,71] particularly in the peri-infarct cortex. This increase in the excitation/inhibition ratio happens within days after stroke and has been noted to resolve outside of the SP.…”
Section: Motor Recovery and Plasticity After Strokementioning
confidence: 99%
“…Additionally, within 3 days after stroke, tonic inhibitory activity is increased. In contrast to phasic inhibition, tonic inhibition is extra-synaptic, controls the overall inhibitory state of a neuronal circuit [71], and is indirectly related to motor recovery after stroke [13]. In a recent study, task-specific motor training, and not just ischemia alone, led to reduced inhibitory markers in a premotor area that mediated recovery [87].…”
Section: Motor Recovery and Plasticity After Strokementioning
confidence: 99%
“…On a cellular level, processes of memory formation and network changes in the poststroke brain are both associated with long‐term potentiation–like phenomena and dendritic spine morphogenesis. On a molecular level, learning and memory paradigms, such as in the hippocampus, are associated with expression changes in stathmin, RB3, GAP43, and the Nogo signaling system, and these same molecular pathways are involved in recovery from stroke 12, 43. An emergent property in neural repair after stroke is that molecular systems that mediate the synaptic plasticity underlying learning and memory are coopted in brain injury to produce recovery of function.…”
Section: The Suffered Is the Learnedmentioning
confidence: 99%